Recent Advances in Chiral Gold Nanomaterials: From Synthesis to Applications - Huangsiyu Chen; Changlong Hao (Molecules)
In recent years, the field of chiral gold nanomaterials has witnessed significant advancements driven by their unique properties and diverse applications in various scientific domains. This review provides an in-depth examination of the synthesis methodologies and evolving applications of chiral gold nanomaterials, which have emerged as vital tools in areas such as antibacterial therapies, biosensing, catalysis, and nanomedicine. We start by discussing various synthesis techniques, focused on seed-mediated growth and circularly polarized light-assisted methods, each contributing to the controlled synthesis of chiral gold nanostructures with tailored optical activities. This review further delves into the applications of these nanomaterials, showcasing their potential in combating antibiotic-resistant bacteria, improving cancer immunotherapy, promoting tissue regeneration, and enabling precise biosensing through enhanced sensitivity and selectivity. We highlight the fundamental principles of chirality and its critical role in biological systems, emphasizing the importance of chiral gold nanomaterials in enhancing optical signals and facilitating molecular interactions. By consolidating recent findings and methodologies, this review endeavors to illuminate the promising future of chiral gold nanomaterials and their critical role in addressing contemporary scientific challenges.